2000
DOI: 10.1111/j.1540-8159.2000.tb00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Dual Site Better Than Single Site Atrial Pacing in the Prevention of Atrial Fibrillation?

Abstract: Long-term prevention of atrial fibrillation is not constantly realized by single-site right atrial pacing, and the beneficial role of multisite atrial pacing is still being studied. Accordingly, we compared the effectiveness of dual site and single site atrial pacing in 83 patients (50 men, 33 women, aged 69 +/- 10 years), who received a DDD device for primary sinus node dysfunction or bradycardia with documented atrial fibrillation. Inclusion criteria for dual site pacing were a sinus P wave > or = 120 ms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…Biatriyal pacing gibi bu süreyi kısaltmaya yönelik tedavi seçenekleri bir çok çalışmada irdelenmiştir ve interatriyal ileti süresinde uzama tespit edilen hasta grubunda, bu yöntemin AF rekürrensinde anlamlı azalma sağla-dığı gösterilmiştir (30)(31)(32).…”
Section: Discussionunclassified
“…Biatriyal pacing gibi bu süreyi kısaltmaya yönelik tedavi seçenekleri bir çok çalışmada irdelenmiştir ve interatriyal ileti süresinde uzama tespit edilen hasta grubunda, bu yöntemin AF rekürrensinde anlamlı azalma sağla-dığı gösterilmiştir (30)(31)(32).…”
Section: Discussionunclassified
“…In comparing these two strategies in patients with prolonged P-wave duration (> 120 msec) at baseline, multisite pacing resulted in less paroxysmal (30% vs 68%) and permanent AF (3% vs 38%). There was no benefit with multisite atrial pacing when compared with the single-site group with P-wave duration less than 120 msec [45]. In a small study of 19 patients, no benefit was found with biatrial pacing compared with RA pacing [46].…”
Section: Multiple Site Atrial Pacing: Chronic Implantationmentioning
confidence: 97%
“…Of note, there was adjustment of antiarrhythmic medications during the study period. Leclercq et al [45] compared the efficacy of multisite atrial pacing (high right atrium and coronary sinus) in 30 patients with single-site atrial pacing in 53 patients. In comparing these two strategies in patients with prolonged P-wave duration (> 120 msec) at baseline, multisite pacing resulted in less paroxysmal (30% vs 68%) and permanent AF (3% vs 38%).…”
Section: Multiple Site Atrial Pacing: Chronic Implantationmentioning
confidence: 99%
“…Special points The SYNBIAPACE (Biatrial Synchronous Pacing for Atrial Arrhythmia Prevention) study showed no difference in time until the first recurrence of AF with biatrial synchronization compared with single-site right atrial pacing. Dual-site pacing shows more promise [24]. The DAPPAF (Dual Site Atrial Pacing to Prevent Atrial experienced centers.…”
Section: Rhythm Control Pacingmentioning
confidence: 99%